(untitled) (Baghdad Science Journal, 2018)
Ankylosing spondylitis is a complex debilitating disease because its pathogenesis is not clear. This study aims at detecting some pathogenesis factors that lead to induce the disease. Chlamydia pneumoniae is one of these pathogenesis factors which acts as a triggering factor for the disease. The study groups included forty Iraqi Ankylosing spondylitis patients and forty healthy persons as a control group. Immunological and molecular examinations were done to detect Chlamydia. pneumoniae in AS group. The immunological results were performed by Enzyme-Linked Immunosorbent Assay (ELISA) to detect anti-IgG and anti-IgM antibodies of C. pneumoniae revealed that five of forty AS patients’ samples (12.5%) were positive for anti-IgG and IgM C. pneumoniae antibodies compared to controls which revealed seronegative. Molecular detection included 16srRNA and HSP-70 genes were to ensure the serological examination for detection of bacteria in the five blood samples which were positive; therefore, these results improved that C. pneumoniae played a role in the pathogenesis of the disease